Anneo Cornuto e gli Stoici romani - Ramelli, Ilaria (Gerión. Revista de Historia Antigua, 2003)
The article offers an analysis of Annaeus Cornutus’ rich intellectual character in the context of the Roman Stoicism of the Neronian age. The topics explored are: his life the sources, his various fields of research (as in the Stoic tradition of Chrysippus, whom he knew well and Crates of Mallus), his influence on Persius, his relations with Nero Seneca and the Stoics of that time. A brief bibliographical appendix concludes the article.